Significance of the Armenian Question - Tunyan, Valery (History and Culture, 2025)
The article analyzes T. Novruzoglu’s concept of the dual meaning of the Armenian Question. Its external aspect is connected with the struggle of the Armenian people for liberation from the exploitation by the surrounding Muslim peoples. The internal aspect appears to be a toolkit for the goals of the leading powers and the implementtation of their national interests. Three phases of the Armenian Question are identified. The first phase is the Russian-Persian War of 1826 - 1828. Its outcome is indicated by the resettlement of Armenians from Iran to the territory of Karabakh in Northern Azerbaijan. The cost of the resettlement of Armenians to the Yerevan and Nakhichevan provinces of Eastern Armenia was 8 000 chervonetses/ducats (10-ruble gold coins), while the cost of the resettlement of Muslim khans and beks with their subjects from the Persian province of Azerbaijan (Atrpatakan) to Eastern Transcaucasia was 20 000 chervonetses. The second phase of the Armenian Question covers the period of the late 19th c. - early 20th c. In World War I, Armenians allegedly destroyed Muslims. It is shown that the Armenian Question is a consequence of the failed modernization of the Ottoman Empire in the late 19th c. - early 20th c, and conflicts of interest of the great powers. These resulted in the Proto-Genocide of 1894-1896 and the Genocide 1915-1923. The third phase of the Armenian Question is considered to be the collapse of the USSR and the Karabakh Question. It is ignored that the Armenian Question is an issue of the existence of the Armenian people from the moment of its coming into existence. It is demonstrated that on December 10, 1991, the Nagorno-Karabakh Autonomous Region, part of Azerbaijan, held a referendum on independence, which was supported by 99.9% of the voters (108,736).